Analisis Faktor-Faktor Keterlambatan Mikrotrans Jak-Lingko Tiba Di Terminal Rawamangun - Muhammad Reza Alim Pratama (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research evaluates delays in the Jak-Lingko Microtrans fleet at Rawamangun Terminal, Jakarta, which faces the main challenge of traffic congestion. Jak-Lingko Mikrotrans is an integrated transportation revitalization program by the DKI Jakarta Provincial Government which aims to increase comfort and ease of mobility for residents. The three main routes studied are JAK 26, JAK 35, and JAK 74. The JAK 26 route connects Duren Sawit with Rawamangun, offering high accessibility but often hampered by traffic jams on main roads such as Jl. Colonel Sugiono and Jl. Youth. The JAK 35 route connects Rawamangun with Pangkalan Jati, passes a number of strategic locations and operates from 05.00-22.00 WIB, but often faces passenger congestion during peak hours. The JAK 74 route connects Rawamangun with Cipinang Muara, via strategic locations such as Klender Station and Deprok Market, but also faces the challenges of congestion and limited coverage. This research aims to analyze the causes of delays and the influence of routes on delays in the Jak-Lingko Mikrotrans fleet arriving at Rawamangun Terminal, using a qualitative descriptive approach to accurately describe the relevant social situation. The research results show that although these routes provide significant benefits for citizen mobility, improvement efforts are needed to overcome the challenges of congestion and operational limitations to increase service efficiency and comfort.